House Rules - Picoult, Jodi 1966- (Thorndike, Me. : Center Point Pub., 2010)
Unable to express himself socially but possessing a savant-like knack for investigating crimes, a teenage boy with Asperger's Syndrome is wrongly accused of killing his tutor when the police mistake his autistic tics for guilty behavior.
Keywords: Asperger's syndrome -- Fiction; Forensic sciences -- Fiction; Criminal investigation -- Fiction; Homicide -- Fiction; Large print books